Safe Sex Perception and HIV Prevention Strategy Among Male Adolescents: A Qualitative Research - Pongtriang, Praditporn; Soontorn, Thassanee (Journal of Research in Nursing-Midwifery and Health Sciences, 2018)
This descriptive qualitative research aimed to study the perception of safe sex and HIV prevention strategy among male adolescents. The research was conducted between December 2016 and March 2018. Participants were nineteen male adolescents aged between 20-26 years. This research project was approved by the Human Research Ethics Committees, Suratthani Rajabhat University. The data were collected by individual in-depth interviews and focus group interviews. The participants were interviewed for 45-60 minutes long with one visit, digitally recorded interviews. The research data gathering from the transcribing process were reviewed for accuracy by the research members and some interview transcripts were randomly reviewed by a participant. Data analysis was conducted by content analysis and using the NVivo 11 for organising the data. The research finding indicated that most participants reflected a barrier of safe sex perception particular the social support, the personal factors such as awareness of protecting a sexual risk behaviour and an access to HIV prevention information. In addition, the participant recommended the strategies raising an effectiveness of HIV prevention among male adolescents particular an increasing of supporting by educational institutions, utilising specific strategies for male adolescents and raising an awareness of prevention to sexual risk behaviour. Based on the research findings, a health organization should encourage the educational institutions to participate in a prevention campaign, as well as to encourage a knowledgeable counsellor to consult appropriately with a context of male adolescents.